Recent Progress in Studying Curcumin and its Nano-preparations for Cancer Therapy - Liu, Jieying; Chen, Siyuan; Lv, Li; Song, Lei; Guo, Shengrong; Huang, Shengtang (Current Pharmaceutical Design, 2013)
A hydrophobic polyphenol compound extracted from turmeric, curcumin has been widely utilized as traditional medicines for centuries in China and India. Over the last decades, because of its low toxicity, extensive studies have been focused on its physicochemical properties and pharmacological activities on various diseases, such as cancer, cardio-vascular disease, inflammatory bowel, wound healing, Alzheimer's disease, rheumatoid arthritis, and diabetes. In particular, bioactivities of curcumin as an effective chemopreventive agent, chemo-/radio-sensitizer for tumor cells, and chemo-/radio-protector for normal organs, are of extraordinary research interests in the literature. Despite these advantages, applications of curcumin are limited in clinical trials because of its poor water solubility and low oral bioavailability. Nano-preparations as an emerging platform for the efficient delivery of anti-cancer drugs should overcome these problems. In this review, we at first briefly revisit important properties of curcumin as well as its uses in cancer treatments, and then overview various nano-preparations of curcumin for cancer therapy, including nanoparticles, liposomes, micelles, nanoemulsions, cyclodextrin complexes, nanodisks, nanofibres, solid lipid nanoparticles, and curcumin conjugates.
Keywords: inflammatory bowel